2021
DOI: 10.1108/bpmj-09-2020-0428
|View full text |Cite
|
Sign up to set email alerts
|

Process maturity and patient orientation in times of a health system reform

Abstract: PurposeThis study investigates the impact of the degree of process maturity on the degree of patient orientation in the context of radical process changes. The study is based on a sample of healthcare providers in Ukraine which experiences a fundamental transformation of its healthcare system.Design/methodology/approachThe investigation was conducted among the full population of the chief physicians from 53 medical institutions (hospitals, general practitioners centers, dental clinics, and maternity clinics) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…A standard deviation of only 10 minutes drives patient utility (and, thus, the overall system welfare) into negative values. Consequently, process standardization is of the highest priority (Bogodistov, Moormann, Sibbel, Krupskyi, & Hromtseva, 2021). The overall utility becomes negative if the processing time is greater than 15 minutes or less than about 7 minutes.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…A standard deviation of only 10 minutes drives patient utility (and, thus, the overall system welfare) into negative values. Consequently, process standardization is of the highest priority (Bogodistov, Moormann, Sibbel, Krupskyi, & Hromtseva, 2021). The overall utility becomes negative if the processing time is greater than 15 minutes or less than about 7 minutes.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Maturity models continue to be developed and operate as a tool that allows organizations to classify their processes according to how they are structured, described, managed, evaluated and optimized (Bogodistov et al, 2022;Dijkman et al, 2015;Lockamy III & McCormack, 2004;Object Management Group, 2008;Oliveira, McCormack, & Trkman, 2012;Ongena & Ravesteyn, 2020;Saravia-Vergara et al, 2020). Specifically, regarding the business process maturity model, developed by the Object Management Group (OMG) and applied in this study from the version adapted by Dijkman et al (2015), we observed the institution of five distinct levels of maturity, used to theoretically understand the respective variable.…”
Section: Development Of Hypothesis and Research Modelmentioning
confidence: 99%
“…Therefore, the conceptual domain of the construct BPMM is defined as the degree of evolution of process management practices undertaken by companies when executing their operations. Such practices are allocated to maturity levels, which result in reporting on the organization’s capabilities to manage its business processes (Bogodistov et al ., 2022; Dijkman et al ., 2015; Object Management Group, 2008; Ongena & Ravesteyn, 2020; Saravia-Vergara et al ., 2020; Sincorá, Dias, Louro, Amaral, & Alvarenga, 2019).…”
Section: Development Of Hypothesis and Research Modelmentioning
confidence: 99%
See 2 more Smart Citations